Telling the truth : the Gospel as tragedy, comedy, and fairy tale - Buechner, Frederick, 1926- (San Francisco : Harper & Row, 1977)
Gift of Union Presby. Church Sustain Trust Fund.
Telling the truth -- The gospel as tragedy -- The gospel as comedy -- The gospel as fairy tale.
Includes bibliographical references.
Keywords: Preaching; Communication -- Religious aspects -- Christianity